2014
DOI: 10.1371/journal.pone.0114262
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intermittent Fasting during the Month of Ramadan in Chronic Haemodialysis Patients in a Tropical Climate Country

Abstract: BackgroundChronic kidney disease is an emerging problem in the majority Muslim countries. Despite the uncertainties of the risks involved, some Muslim patients undergoing chronic haemodialysis choose to observe intermittent fasting during the month of Ramadan. This study aims to investigate the effect of Ramadan fasting in haemodialysis patients residing in a tropical climate country.MethodsThis prospective cross sectional study recruited Muslim patients on regular haemodialysis from three haemodialysis centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
(28 reference statements)
7
11
2
Order By: Relevance
“…One study reported that Ramadan fasting was associated with increase in mean IDWG by 0.6 kg among Saudi hemodialysis patients [20]. Other studies reported that Ramadan fasting was associated with either decrease or no significant difference in IDWG [3, 22, 24, 25]. The underlying mechanisms for our observation of increasing mean IDWG in RFG and RPFG is not clear, as our study did not collect dietary information.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…One study reported that Ramadan fasting was associated with increase in mean IDWG by 0.6 kg among Saudi hemodialysis patients [20]. Other studies reported that Ramadan fasting was associated with either decrease or no significant difference in IDWG [3, 22, 24, 25]. The underlying mechanisms for our observation of increasing mean IDWG in RFG and RPFG is not clear, as our study did not collect dietary information.…”
Section: Discussionmentioning
confidence: 72%
“…Some studies have reported that Ramadan fasting was associated with significant changes in clinical and biomedical markers, such as fluid overload and hyperkalemia, but with no significant complications requiring hospitalization [3, 20]. Other studies found no clinically important variations in biomedical markers in hemodialysis patients during Ramadan fasting [21, 22]. Due to the lack of clear evidence about the safety of Ramadan fasting by CDK and hemodialysis patients, the International Diabetes Federation and Ramadan International Alliance consider these patients to be at very high risk, and are, therefore, exempted from Ramadan fasting.…”
Section: Introductionmentioning
confidence: 99%
“…In HD subjects with dyslipidemia (high plasma triacylglycerol (TAG) and low high-density lipoprotein cholesterol (HDL-C) concentrations), changes in dietary habits (as in the case during R), regardless of whether subjects opt to fast the entire stretch or fast for only a portion of the R period, may affect circulating lipoproteins. There is however limited information available on alterations in plasma lipids [30] during the period of R in HD patients. Wan Md Adnan et al [30] noted decreased low-density lipoprotein cholesterol (LDL-C) concentrations at the end of R in diabetic HD patients, while Adanan et al [29] reported no effects on LDL-C. Mixed results have also been obtained in healthy individuals where increased LDL-C and lower TAG [15], or no effects on LDL-C [31] or decreased LDL-C [29,32] have been observed during the R period.…”
Section: Introductionmentioning
confidence: 99%
“…There is however limited information available on alterations in plasma lipids [30] during the period of R in HD patients. Wan Md Adnan et al [30] noted decreased low-density lipoprotein cholesterol (LDL-C) concentrations at the end of R in diabetic HD patients, while Adanan et al [29] reported no effects on LDL-C. Mixed results have also been obtained in healthy individuals where increased LDL-C and lower TAG [15], or no effects on LDL-C [31] or decreased LDL-C [29,32] have been observed during the R period. In contrast, a meta-analysis in healthy subjects during R found a significant reduction in LDL in both genders, a significant reduction in total cholesterol and TAG amongst males and a significant increase in HDL-C among females [16].…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent fasting generally entails normal intake for 5 d a week, but intake of a quarter of the normal calories for the other 2 d (usually 500 calories for females, 600 calories for males). A multicenter and large sample research demonstrated that patient body weight was reduced by 4.3 kg on average after 6 wk of intermittent fasting[ 30 ]. Halberg et al[ 31 ] found that healthy people who underwent 2 wk of intermittent fasting exhibited no obvious body weight loss, but they did show improved insulin sensitivity - that is, the capacity for glucose storage and fat decomposition was increased.…”
Section: Behavioral and Psychological Interventionmentioning
confidence: 99%